Grassroots participation in policy processes and service delivery: a case study of the western Cape provincial department of social services.: - Mpinda, Siyavuya (University of the Western Cape, 2021)
Masters in Public Administration - MPA === Grassroots participation in the domain of public policy is assuming global significance particularly in the fields of welfare and development. Revived by the United Nations' resolution in the 1970s, many governments both in developed and underdeveloped countries have endorsed the grassroots participation ideals as contained in the United Nations' policy statements and resolutions. Accordingly, many governments have declared their support for grassroots participation and in number of cases, grassroots participation has featured conspicuously in their national development plans. _. A late arrival on the grassroots participation discourse, grassroots participation and civil society's involvement have also featured predominantly in the national development plans of the new South African government. The new democratically elected government pronounced in various policy documents and on public platforms, a commitment towards grassroots participation. Although many governments have employed the rhetoric of grassroots participation in their national·. development plans, there is however an accumulative literature which points to the fact that grassroots participation endeavors have· often been undertaken in a top-down fashion, with marginalized groups of communities often excluded. The central objective of this study has therefore been a critical evaluation of the manner in which the Western Cape Provincial Department of Social Services has implemented its grassroots approach in the context of policy. formulation and implementation and service delivery. An evaluation of the Department's grassroots approach has been attempted by assessing the grassroots structures, which the Department has established as vehicles for grassroots participation in its policy processes and service delivery. To this end, of Fourteen District Committees established by the Department throughout the Western Cape province, four have been evaluated. Through reviewing literature Oh grassroots participation, the project's findings highlighted a discrepancy between the Department's prevailing rhetoric of grassroots participation and the reality of the grassroots participation as operationalized through these committees. The findings indicated that the grassroots participation through these committees is far from the ideal of authentic grassroots participation as discussed in Chapter Two, as it is replete with elements of unrepresentativeness of the marginalized groups, co-option, political manipulation, centralized and top-down decision-making styles. The study also attempted to provide recommendations tailored to bring the Department's grassroots participatory process closer to the ideals of authentic